2019
DOI: 10.1007/s00430-019-00598-6
|View full text |Cite
|
Sign up to set email alerts
|

Generation, maintenance and tissue distribution of T cell responses to human cytomegalovirus in lytic and latent infection

Abstract: Understanding how the T cell memory response directed towards human cytomegalovirus (HCMV) develops and changes over time while the virus persists is important. Whilst HCMV primary infection and periodic reactivation is well controlled by T cell responses in healthy people, when the immune system is compromised such as post-transplantation, during pregnancy, or underdeveloped such as in newborn infants and children, CMV disease can be a significant problem. In older people, HCMV infection is associated with in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 109 publications
1
39
0
1
Order By: Relevance
“…23,45,46 Memory inflation of CMV-specific T cells in humans was questioned recently. 47 Longitudinal studies in humans are very limited, and some report evidence for memory inflation, 40,48 while others do not. 49,50 Our study allowed us to investigate how duration of CMV infection influences the T-cell memory pool in humans.…”
Section: Discussionmentioning
confidence: 99%
“…23,45,46 Memory inflation of CMV-specific T cells in humans was questioned recently. 47 Longitudinal studies in humans are very limited, and some report evidence for memory inflation, 40,48 while others do not. 49,50 Our study allowed us to investigate how duration of CMV infection influences the T-cell memory pool in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this result from MCMV models, infective augmentation after HCMV immunization could be a possibility. Some of these concerns were alleviated by a cohort study in human volunteers, where no suppressive phenotype was found after lifelong HCMV carriage [176]. Another biosafety issue focuses on the relevance of viral coinfection and its impact on MI, specifically as HIV + CMV + individuals show inflation of CMV epitope-specific CD4 T cells [177].…”
Section: Cd4 T Cellsmentioning
confidence: 99%
“…I cannot highlight here all the outstanding contributions, but, in editor's view, most challenging for all 'mouse modelers' is the contribution by Jackson and colleagues [4] who conclude "that there is only limited evidence supportive of memory inflation occurring in humans", a conclusion that contradicts the generalized statement found in almost all papers on MI in animal models, namely that "MI is a hallmark of CMV infections". In accordance with missing MI in most human CMV-seropositive but otherwise healthy volunteers, previous protagonists of CMV-associated immunosenescence appear to back away from a relevance in humans [5] and a systematic review and meta-analysis in influenza vaccinees by van den Berg and colleagues [6] arrives at the conclusion "that there is no unequivocal evidence that latent CMV infection affects the influenza antibody response to vaccination".…”
mentioning
confidence: 90%